Exploring materialism and frugality in determining product end‐use consumption behaviors. Issue 12 (27th September 2018) - Evers, Uwana; Gruner, Richard L.; Sneddon, Joanne; Lee, Julie A.
Abstract: Materialism is often blamed for consumers' unsustainable consumption behaviors and its contribution to a growing "throwaway culture." Conversely, frugal consumers are regarded as both restrained in their acquisition, and resourceful in their use and disposal of products. In this paper, the authors challenge and empirically test these prevailing beliefs. The authors focus on a much‐neglected aspect of the consumption continuum: the disposal of products at the end‐use of consumption, and how key consumer traits (i.e., materialism and frugality) influence behaviors at this stage. Specifically, the authors examined three creative end‐use consumption behaviors with a sample of 398 US consumers. Results support the counter‐intuitive notion that materialism, alongside frugality, has a positive impact on consumers' sustainable consumption behaviors. The data suggest that materialistic consumers are prone to finding new and different uses for products and alternative methods of product disposal. The study's results also support the notion that frugality interacts with materialism to increase intentions to find alternative methods of product disposal. The authors discuss the implications pertaining to their findings and pave the way for future research in sustainable consumption.